Bury me at the marketplace : Es'kia Mphahlele and company, letters 1943-2006 - Mphahlele, Es'kia, 1919-2008 (Wits University Press, 2010)
When Chabani Manganyi published the first edition of selected letters twenty-five years ago as a companion volume to "Exiles and Homecomings: A Biography of Es'kia Mphahlele", the idea of Mphahlele's death was remote and poetic. The title, "Bury Me at the Marketplace", suggested that immortality of a kind awaited Mphahlele, in the very coming and going of those who remember him and whose lives he touched. It suggested, too, the energy and magnanimity of Mphahlele, the man, whose personality and intellect as a writer and educator would carve an indelible place for him in South Africa's public sphere. That death has now come and we mourn it. Manganyi's words at the time have acquired a new significance: in the symbolic marketplace, he noted, 'the drama of life continues relentlessly and the silence of death is unmasked for all time'. The silence of death is certainly unmasked in this volume, in its record of Mphahlele's rich and varied life: his private words, his passions and obsessions, his arguments, his loves, hopes, achievements, and yes, even some of his failures. Here the reader will find many facets of the private man translated back into the marketplace of public memory. Despite the personal nature of the letters, the further horizons of this volume are the contours of South Africa's literary and cultural history, the international affiliations out of which it has been formed, particularly in the diaspora that connects South Africa to the rest of the African continent and to the black presence in Europe and the United States. This selection of Mphahlele's own letters has been greatly expanded; it has also been augmented by the addition of letters from Mphahlele's correspondents, among them such luminaries as Langston Hughes and Nadine Gordimer. It seeks to illustrate the networks that shaped Mphahlele's personal and intellectual life, the circuits of intimacy, intellectual inquiry, of friendship, scholarship and solidarity that he created and nurtured over the years. The letters cover the period from November 1943 to April 1987, forty-four of Mphahlele's mature years and most of his active professional life. The correspondence is supplemented by introductory essays from the two editors, by two interviews conducted with Mphahlele by Manganyi and by Attwell's insightful explanatory notes.
Keywords: Mphahlele, Es'kia, -- 1919-2008 -- Correspondence.; Mphahlele, Es'kia, -- 1919-2008; Authors, South African -- 20th century -- Correspondence.; South Africa -- Intellectual life -- 20th century.; Écrivains sud-africains -- 20e siècle -- Correspondance.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; BIOGRAPHY & AUTOBIOGRAPHY / General; Authors, South African; Intellectual life; South Africa; 1900-1999; Personal correspondence